Relationship between academic procrastination, coping and sense of coherence among undergraduates in Malaysia - Leela, Murugan; Loo, Ling Qian; Tan, Man Ting (2021)
Academic procrastination is a serious issue among Malaysian undergraduates. The present study aimed to examine the relationship between academic procrastination, coping and sense of coherence among Malaysian undergraduates as well as to determine the significant predictor of academic procrastination. Using a quantitative, descriptive and cross-sectional research design with purposive sampling method, 99 respondents (n=99), aged 19 to 24 (M = 22.36; SD = 1.28) were recruited for the actual study despite from 30 respondents for the pilot study with the same data collection procedure, sending Qualtrics online survey throughout social networking sites within Malaysian context. The study’s inclusive criterion was Malaysian undergraduates aged 18 to 24 while the exclusive criterion was international students. Measurements included self-reported Orientation to Life Questionnaire (SOC-13), Brief-COPE and Aitken Procrastination Inventory. Pearson correlation showed academic procrastination was negatively associated with emotion-focused and problem-focused coping, but positively associated with avoidant coping. Academic procrastination was negatively correlated with sense of coherence. Sense of coherence was positively associated with emotion-focused and problem-focused coping, but negatively correlated with avoidant coping. Multiple Linear Regression indicated avoidant coping (consistent to previous studies which stated students who applied avoidant coping tended to procrastinate) and sense of coherence with item-10 deleted (new findings in the present study) significantly predicted academic procrastination. Limited study in Malaysia context motivated further research within this topic and to adopt suitable measure to deal with academic procrastination.